The Role of Interpersonal Communication Between Teachers and High School’s Students in Overcome Bullying Behavior - Mardhiyyah Mardhiyyah; Ghazali Ama La Nora; MA. Theresa Bringas Nardo (Lembaga penelitian dan pengabdian kepada masyrakat, 2021)
Bullying is aggressive behavior or action that involves an imbalance of power that is detrimental to others. Most bullying occurs at school and a lot of data can prove that schools are the biggest contributors to bullying behavior. The output of this community services is Being able to provide an understanding of the importance of creating conditions and a good and comfortable school atmosphere for students to avoid bullying behavior at school. This community services held with lecture method accompanied by an explanation and interactive discussion involving all participants. The implementation of this Community Service is going well and smoothly. The success factor of this Community Service activities at MAN 10 Jakarta is the enthusiasm of participants in receiving material and communicative material delivery by the Speakers. While the obstacle in this activity is the unavailability of credible resource persons and the limited time to carry out the Activity.